Fratelli d’Italia, Christian identity, and claim–audience congruence - Adinolfi, G. (European Politics and Society)
This paper analyses how Fratelli d’Italia (Brothers of Italy – FdI) articulates Christianity as a repertoire of representative claims and tests their congruence with the party’s electorate. The argument is that representation is a performative act arising from the interaction between claim-maker and audience, and that identity must be read within the enduring social salience of Catholicism in Italy. While the literature on FdI is extensive, the intersection of religion, representation and audience has received relatively little systematic attention. Building on Saward’s theory of representative claims, representation is theorised as a process requiring audience recognition. Methodologically, the study combines discourse analysis of party texts with ITANES and ESS survey data (2018–2023). Three hypotheses guide the analysis: that FdI’s religious and value-based claims resonate with its electorate; that congruence is shaped by broader cultural cleavages; and that symbolic belonging carries more weight than religious practice. The findings suggest that FdI’s Christian-national repertoire broadly ‘lands’ among its voters: there is congruence between the claim-maker’s discourse (the party and its leader) and the audience (its electorate). Religion functions as an identity marker that draws a sharp boundary between ‘us’ and ‘them’, with symbolic belonging resonating more strongly than regular religious practice.